Parental support, personality, self-efficacy as predictors for depression among medical students - Nasir R., Mustaffa M. B., Wan Shahrazad W. S., Khairudin R., Syed Salim S. S. (N/A, 2011)
Parental support, personality, self-efficacy as predictors for depression among medical students by Nasir R., Mustaffa M. B., Wan Shahrazad W. S., Khairudin R., Syed Salim S. S.,